Older adults' experiences of wellbeing during the COVID-19 pandemic: a comparative qualitative study in Italy and Switzerland - Dones, Iuna; Ciobanu, Ruxandra Oana (Frontiers in Sociology, 2024)
Background: Particularly at the beginning of the pandemic, adults aged 65 and older were portrayed as a homogeneously vulnerable population due to the elevated health risks associated with contracting the COVID-19 disease. This portrayal, combined with travel restrictions, closures of economic sectors, country-wide lockdowns, and suggestions by governmental authorities to limit social contact, had important implications for the well-being of older individuals. However, older adults are a heterogeneous population who relies on different resources to cope with stressful periods, like the COVID-19 pandemic. Simultaneously, countries also employed different measures to contain the virus. Research thus far has focused on the short-term consequences of the pandemic, but studies have yet to address its long-term consequences.Objectives: We explore older adults' lived experiences nearly two years after the pandemic onset. Moreover, we focus on the bordering countries of Switzerland and Italy, who employed contrasting containment measures. This paper analyzes 1) How the COVID-19 pandemic impacted the experiences of well-being of older adults in these regions and 2) How older adults coped with the stressors brought about by the pandemic, in particular social distancing. Methods: The paper draws on 31 semi-structured interviews with 11 Swiss natives residing in Switzerland, 10 Italian migrants residing in Switzerland, and 10 Italian natives residing in Italy. Interviews were conducted from December 2021 to March 2022. Results: Coping mechanisms of the three groups related to acceptance, hobbies, cognitive reframing, telephone use, vaccine use and social distancing. However, results show heterogeneous experiences of well-being, with Swiss natives sharing more positive narratives than the other two groups. Moreover, Italian migrants and Italian natives expressed the long-term negative consequences of the pandemic on their experienced well-being